On the sand - Hunt,Roderick (Oxford university press, 1986)
"On the Sand" by Roderick Hunt, part of the Oxford Reading Tree series, features Biff, Chip, Kipper, and their friends as they enjoy a day at the beach. The story revolves around their fun activities, such as building sandcastles and playing games in the sand.
Keywords: Textbook